The pathway to the top: Key factors and influences in the development of Australian Olympic and World Championship Track and Field athletes - Huxley, D. J.; O`Connor, D.; Larkin, P. (International Journal of Sports Science & Coaching, 2017)
Given the many benefits of international sporting success, understanding the development and long-term sustainability of an elite sporting career has become an important pursuit worldwide. Despite decades of research little is known about the development of elite senior Australian Track and Field athletes, therefore this study aimed to understand the major influences contributing to their development and success. A Track and Field Athlete Development questionnaire was used to collect data from 73 Olympic and World Championship level athletes. Analysis indicated athletes progressed to the elite level via six different pathways; however, the majority follows a linear pathway from junior to elite senior athlete. Further, results demonstrated the key influencing factors during development included later specialization, involvement in other sports during adolescence and strong social support. In addition, growing up in a major city and completing a University degree were also common features. Overall the study provides an insight into the development and success of Australian Track and Field athletes who competed at the Olympic Games or World Championships between 1956 and 2013. FROM AUTHOR